Answer:
<em>3.1405</em>
Step-by-step explanation:
= 1 ⇒ This is always the case
So,
3.1405 × 1 = 3.1405
Answer:
hope it helps you thank you
Step-by-step explanation:
mark me as brilliant
The solutions of the function are:
- When f(x) = -4, the solution is -4
- When f(x) = -2, the solution is -5/2
- When f(x) = 0, the solution is -1
<h3>How to solve for the equation </h3>
The equation is given as
When x = -4
3/4 * -4 -1
= -12/4 - 1
= -4
When x = -2
3/4*(-4) - 1
= -6/4 - 1/1
Take the lcm
-10/4
= -5/2
When x = 0
3/4(0) - 1
= -1
When f(x) = -4, the solution is -4
When f(x) = -2, the solution is -5/2
When f(x) = 0, the solution is -1
Read more on real numbers here:
brainly.com/question/155227
#SPJ1
Answer:
Step-by-step explanation:
1. use the distance formula!
2. then using the distance formula with (2, 7) and (-6, -2) you get...
is the simplest radical form
:D
Answer:
answer B: (2,-2)
Step-by-step explanation:
First, write the equations on top of each other:
Then, multiply the the second equation by 2 so that we can use elimination of the y-variable:
Next, use elimination to find the value of "x":
So, your x-value is 2.
Now, substitute your x-value into one of your equations, let's take the second equation, 2x-y=6:
Your y-value is -2.
With all your information gathered, you find that the solution to this system of equation is (2,-2).